Elevated Levels of Specific Carotenoids During Acclimation to Strong Light Protect the Repair of Photosystem II in Synechocystis sp. PCC 6803 - Izuhara, Taichi; Kaihatsu, Ikumi; Jimbo, Haruhiko; Takaichi, Shinichi; Nishiyama, Yoshitaka (Frontiers in Plant Science, 2020)
The tolerance of photosynthesis to strong light increases in photosynthetic organisms during acclimation to strong light. We investigated the role of carotenoids in the protection of photosystem II (PSII) from photoinhibition after acclimation to strong light in the cyanobacterium Synechocystis sp. PCC 6803. In cells that had been grown under strong light at 1,000 μmol photons m-2 s-1 (SL), specific carotenoids, namely, zeaxanthin, echinenone and myxoxanthophyll, accumulated at high levels, and the photoinhibition of PSII was less marked than in cells that had been grown under standard growth light at 70 μmol photons m-2 s-1 (GL). The rate of photodamage to PSII, as monitored in the presence of lincomycin, did not differ between cells grown under SL and GL, suggesting that the mitigation of photoinhibition after acclimation to SL might be attributable to the enhanced ability to repair PSII. When cells grown under GL were transferred to SL, the mitigation of photoinhibition of PSII occurred in two distinct stages: a first stage that lasted 4 h and the second stage that occurred after 8 h. During the second stage, the accumulation of specific carotenoids was detected, together with enhanced synthesis de novo of proteins that are required for the repair of PSII, such as the D1 protein, and suppression of the production of singlet oxygen (1O2). In the crtRcrtO mutant of Synechocystis, which lacks zeaxanthin, echinenone and myxoxanthophyll, the mitigation of photoinhibition of PSII, the enhancement of protein synthesis, and the suppression of production of 1O2 were significantly impaired during the second stage of acclimation. Thus, elevated levels of the specific carotenoids during acclimation to strong light appeared to protect protein synthesis from 1O2, with the resultant mitigation of photoinhibition of PSII.